INDONESIAS FUEL SUBSIDY A SAD HISTORY OF MASSIVE POLICY FAILURE - Howard Dick (Masyarakat Indonesia, 2013)
In her path-breaking economic history of Indonesia, A History of MissedOpportunities, Anne Booth aptly summarizes the sad history of fuel policy inIndonesia since 1980. The escalation of fuel subsidies whenever there is an upwardtrend in international prices and the failure to terminate them when prices fall shouldalert economists to some very discomforting messages. First, governments are notreceptive to policy measures that involve short-term political pain and have very littleawareness or interest in opportunity cost. Second, while governments pay lip serviceto the environment and express concern about global warming, they are not yet willingto make it a policy priority. Third, populism is the very essence of politics and hasbecome more so in the democratic era. The lesson of history is that governmentscannot be trusted to set energy prices. Nor is there any good reason to do so. Whatgovernments should do is to monitor the prices being set by Pertamina as a stateowned monopoly and provide temporary welfare support if and when it can be justifiedby any sudden escalation in domestic prices.Keywords: Fuel subsidy, Oil price, Pertamina.